The art of urban design in urban regeneration : interdisciplinarity, policies, governance, public space - Remesar, Antoni (Col·lecció Comunicació Activa, 2016)
This volume comprises transcripts of the presentations made at the International seminar "CITIES. Interdisciplinary Issues in Urban Regeneration, Urban Design, Public Art and Public Space", organized by the POLIS Research Centre and the PAUDO (Public Art and Urban Design Observatory) network in December 2013. The book traces the paths of economic and political theory concerning the role of urban regeneration processes, from an overview of the policies implemented in Europe to their actual impact on job creation and local innovation initiatives. It addresses physical aspects of urban design processes, analysing an interdisciplinary project for urban regeneration of the Lisbon riverfront, and proposes some ideas on how to deal with climate change in the construction of public space in cities. Finally, the book concludes with a reflection on new modes of urban governance that can make an urban environment more liveable, evaluating the involvement of neighbours reconvertint their role from consultive partners to active participants in the physical (urban design) and symbolic (public art) transformation of their communities. Thus, the book encompasses a broad reflection on urban regeneration, with contributions from disciplinary fields as diverse as Economics, Public Policy, Urban Design and Architecture, Landscaping and Public Art, and draws attention to the need for further interdisciplinary work.